INTERACTIVE SOUND TOOLS AND ENGINES - BORZA, Adrian (Studia Universitatis Babes-Bolyai Musica, 2018)
The compositional algorithms are recognized as solutions to music problems which appear in computer programming. They are small to large-sized patches designed for analyzing, for example, the direction, size, and the magnitude of change of a melodic interval; analyzing the rest between two MIDI events; analyzing the register, duration, delta time and dynamics of MIDI events; analyzing the number of notes of a chord; storing, limiting and sorting pitch or intensity values; processing MIDI events; making chord progressions; compositing a canon; tracking a musical MIDI score.